Papers literary, scientific, &c. by the late Fleeming Jenkin - Jenkin, Fleeming, 1833-1885 (ICE Publishing, 2011)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present.
Keywords: Science.; Economics.; Graphic methods.; Cables, Submarine.; elektronické knihy; electronic books